Decarbonizing the pulp and paper industry: A critical and systematic review of sociotechnical developments and policy options. (October 2022) - Furszyfer Del Rio, Dylan D.; Sovacool, Benjamin K.; Griffiths, Steve; Bazilian, Morgan; Kim, Jinsoo; Foley, Aoife M.; Rooney, David
Abstract: Paper has shaped society for centuries and is considered one of humanity's most important inventions. However, pulp and paper products can be damaging to social and natural systems along their lifecycle of material extraction, processing, transportation, and waste handling. The pulp and paper industry is among the top five most energy-intensive industries globally and is the fourth largest industrial energy user. This industry accounts for approximately 6% of global industrial energy use and 2% of direct industrial CO2 emissions. The pulp and paper industry is also the largest user of original or virgin wood, with deleterious impacts on both human health and local flora and fauna, including aquatic ecosystems. This critical and systematic review seeks to identify alternatives for mitigating the climate impacts of pulp and paper processes and products, thus making the pulp and paper industry more environmentally sustainable. This study reviews 466 studies to answer the following questions: what are the main determinants of energy and carbon emissions emerging from the pulp and paper industry? What are the benefits of this industry adopting low-carbon manufacturing processes, and what barriers will need to be tackled to enable such adoption? Using a sociotechnical lens, we answer these questions, identify barriers for the pulp and paper industry's decarbonization, and present promising avenues for future research. Highlights: This review identifies carbon-intensive processes in the pulp and paper industry. Presents decarbonizing practices, potential transformations and innovations. Presents promising avenues for future research. No agreed consensus on the most promising technologies to achieve net-zero in the pulp and paper industry. Pulp and paper products are associated with other sociotechnical systems that create compelling interdependencies among industries.